Benchtop Porosity Measurement Technique Using Electrical Capacitance Tomography (ECT) Sensor - Ali, Mohamad Farid (Universiti Teknologi PETRONAS, 2014)
This report consists of five chapters which are introduction, literature review, methodology, expected results and conclusion. The introduction of the report mentioned the background study of the project, followed by problem statement, objectives and the scope of study. The main objective of this project is to design a sensor called Electrical Capacitance Tomography (ECT) to measure porosity in a core sample. The conventional techniques used in lab, using Helium Porosimeter and Water Saturation methods are performed for comparison purposes. The literature review explained about the research done on topics, related to the project such as the design of ECT sensor and porosity measurement. ECT sensor is used to visualize and measure the permittivity distribution of a cross sectional area of vessel. The measurement is done by using multi-electrode capacitance sensor. For the methodology, it consisted of research methodology process flow, the project activities with the aid of key milestones diagram, the tools needed for the success of the project and experimental procedure to run the experiment. The project started by designing and fabricating the ECT Sensor. The ECT Sensor would then be used to measure porosity of core sample. The result will be in terms of tomography image, and porosity of the rock sample would then be measured. The porosity measured from ECT sensor would be compared with the conventional technique of porosity measurement in lab to identify the effectiveness of ECT sensor in measuring porosity. Based on the result, the measurement of ECT shows error more than 10% of the porosity value measured using helium porosimeter and water saturation technique. The ECT sensor may not be effective to measure porosity, yet with further improvement, the possibility of measuring and visualizing the porosity distribution of core sample can be done.